Poly(hydroxyethyl methacrylate)‐based composite cryogel with embedded macroporous cellulose beads for the separation of human serum immunoglobulin and albumin. Issue 24 (18th November 2013) - Ye, Jialei; Yun, Junxian; Lin, Dong‐Qiang; Xu, Linhong; Kirsebom, Harald; Shen, Shaochuan; Yang, Gensheng; Yao, Kejian; Guan, Yi‐Xin; Yao, Shan‐Jing
<x xml:space="preserve">Abstract</x> A novel super‐macroporous monolithic composite cryogel was prepared by embedding macroporous cellulose beads into poly(hydroxyethyl methacrylate) cryogel. The cellulose beads were fabricated by using a microchannel liquid‐flow focusing and cryopolymerization method, while the composite cryogel was prepared by cryogenic radical polymerization of the hydroxyethyl methacrylate monomer with poly(ethylene glycol) diacrylate as cross‐linker together with the cellulose beads. After graft polymerization with (vinylbenzyl)trimethylammonium chloride, the composite cryogel was applied to separate immunoglobulin‐G and albumin from human serum. Immunoglobulin‐G with a mean purity of 83.2% and albumin with a purity of 98% were obtained, indicating the composite cryogel as a promising chromatographic medium in bioseparation for the isolation of important bioactive proteins like immunoglobulins and albumins.